Detection of Overhead Contact Lines with a 2D-Digital-Beamforming Radar System for Automatic Guidance of Trolley Trucks. (6th March 2013) - Harter, Marlene; Schipper, Tom; Zwirello, Lukasz; Ziroff, Andreas; Zwick, Thomas
Abstract : The benefit of trolley truck systems is the substitution of the diesel fuel by the cheaper and more ecological electrical energy. Trolley trucks are powered by electricity from two overhead contact lines, where one is the supply and the other the return conductor. Such trolley trucks are used for haulage at open pit mining sites but could also be used for freight traffic at roadways in the future. Automatic guidance prevents the trolley-powered trucks from leaving the track and thus allows higher operating speeds, higher loading capacity, and greater efficiency. Radar is the ideal sensing technique for automatic guidance in such environments. The presented radar system with two-dimensional digital beamforming capability offers a compact measurement solution as it can be installed on top of the truck. Besides the distance measurement, this radar system allows to detect the location and inclination of the overhead contact lines by digital beamforming in two dimensions. Besides automatic guidance, the knowledge of the inclination of the overhead contact lines could allow automatic speed adaption, which would help to achieve maximum speed especially in hilly terrain.